Oil price risk in selected ASEAN markets - Mansor H. Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper analyzes the oil price risk in four ASEAN markets using a two-factor "market and oil" model and EGARCH(1, 1) variance specification. In the analysis, three alternative non-linear measures of oil prices are used and robustness check of basic results is also performed. The results suggest a direct relation between oil price changes and stock market returns and indicate no evidence for asymmetric oil price risk for Indonesia. Meanwhile, the asymmetric oil price risk seems apparent for the markets of Malaysia, Singapore and Thailand. For an oil exporting Malaysia, the oil price decline tends to compromise its market performance while the oil price increase does not seem to be beneficial. In contrast, for oil-importing Singapore and Thailand, the oil price shocks tend to adversely affect their market returns. The contrasting experiences of these markets in the face of oil price fluctuations are attributed to the degree of oil dependency, level of financial development, and trade openness.